2020
DOI: 10.5152/eurjrheum.2019.19072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subclinical myocardial dysfunction using speckle tracking echocardiography in patients with radiographic and non-radiographic axial spondyloarthritis

Abstract: European Journal of Rheumatology (Eur J Rheumatol) is an international, open access peer reviewed journal committed to promoting the highest standards of scientific exchange and education. The journal is published quarterly on January, April, July and October.The aim of the European Journal of Rheumatology is to cover various aspects of rheumatology for its readers, encompassing the spectrum of diseases with arthritis, musculoskeletal conditions, autoinflammatory diseases, connective tissue disorders, osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…By 2 D STE we find that AS patients has subclinical myocardial systolic dysfunction compared to the control. In this study AS increase in patient with overweight BMI from 25-29.9 kg/m2 (40% of patients) due to limitation of movements and exercises that results from severe pain , and more in negative family history of disease that agree with Emren et al (31) that show mean BMI 24±4.3, more in male than female this agree with El Maghraoui et al (4) and Emren et al (31) . More in non-smoker with limited physical activity which disagree with Emren et al (31) that show the increasing of AS disease among positive smoking due to their habits .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…By 2 D STE we find that AS patients has subclinical myocardial systolic dysfunction compared to the control. In this study AS increase in patient with overweight BMI from 25-29.9 kg/m2 (40% of patients) due to limitation of movements and exercises that results from severe pain , and more in negative family history of disease that agree with Emren et al (31) that show mean BMI 24±4.3, more in male than female this agree with El Maghraoui et al (4) and Emren et al (31) . More in non-smoker with limited physical activity which disagree with Emren et al (31) that show the increasing of AS disease among positive smoking due to their habits .…”
Section: Discussionsupporting
confidence: 88%
“…In this study AS increase in patient with overweight BMI from 25-29.9 kg/m2 (40% of patients) due to limitation of movements and exercises that results from severe pain , and more in negative family history of disease that agree with Emren et al (31) that show mean BMI 24±4.3, more in male than female this agree with El Maghraoui et al (4) and Emren et al (31) . More in non-smoker with limited physical activity which disagree with Emren et al (31) that show the increasing of AS disease among positive smoking due to their habits . In our study we find significant reduction in GLS % -18.32±3.39 :p=0.047 of AS patient in comparison with control, this agree with other study like Ustun et al (13) show that by STE, there was reduction in myocardial systolic function in AS patients , in absence of CVD.…”
Section: Discussionsupporting
confidence: 88%
“…Three studies assessed diastolic LV dysfunction using the combined set of parameters as recommended by the ASE/EACVI in 2009, ranging from 12% to 45%, though cut-off values of single parameters differed slightly between studies [ 15 , 29 , 30 ]. Other studies reported prevalence rates ranging from 20% to 49%, but those studies were not specifically designed to assess diastolic LV dysfunction or only used a single or few echocardiographic parameters for assessing diastolic LV dysfunction, which differs from the ASE/EACVI guidelines [ 8 , 14 , 26 , 31 , 32 , 33 , 34 ]. Nowadays, the most appropriate way, recommended by American and European echocardiography organizations (ASE and EACVI), to assess diastolic LV dysfunction, is to combine specific echocardiographic parameters [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, Kiltz U et al [15] who reported significant difference in sex between the patients in the radiographic and non-radiographic axial spodyloarthritis groups (76.8% male AS patients versus 31.8% male nr-axSpA patients), while Bath Ankylosing Spondylitis Disease Activity Index did not differ between both groups. Also, Emren et al [16] found differences in inflammatory activity (CRP) and gender ratio between AS and nr-axSpA.…”
Section: Discussionmentioning
confidence: 98%